2016
DOI: 10.1016/j.actamat.2015.09.053
|View full text |Cite
|
Sign up to set email alerts
|

The indirect influence of the ω phase on the degree of refinement of distributions of the α phase in metastable β-Titanium alloys

Abstract: Non-conventional transformation pathways have been exploited to determine the degree of refinement of the microstructure of a metastable -Ti alloy. This has involved a set of heattreatments where samples, initially quenched to room temperature (RT) from above the  transus are slowly heated to 350°C, then isothermal annealed at 350°C for various times prior to upquenching to 600°C and again isothermally annealed at that temperature, followed by quenching to RT. Interrupted treatments have also been performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(51 citation statements)
references
References 17 publications
(42 reference statements)
2
48
0
1
Order By: Relevance
“…On the other hand, isothermal ω structure develops after subsequent annealing at a temperature below ω solvus. After prolonged aging, isothermal ω is known to promote α phase either directly by acting as heterogeneous nucleation sites or indirectly [17][18][19][20]. It is known that ω structure is formed due to collapse of {111} planes in β phase [14,15].…”
mentioning
confidence: 99%
“…On the other hand, isothermal ω structure develops after subsequent annealing at a temperature below ω solvus. After prolonged aging, isothermal ω is known to promote α phase either directly by acting as heterogeneous nucleation sites or indirectly [17][18][19][20]. It is known that ω structure is formed due to collapse of {111} planes in β phase [14,15].…”
mentioning
confidence: 99%
“…Typically, the -phase is undesirable as it embrittles the alloy [10]; it is, however, generally believed to be a precursor to the formation of stable nanoscale -precipitates that highly strengthen the alloy [8,9,13,14]. This precipitation sequence is not fully understood, and a vast amount of APT research has been published recently to help further our insight into the precipitation mechanisms of the high-strengthto-weight -Ti alloys: Ti-5Al-5Mo-5V-3Cr wt.% (Ti-5553); and Ti-6Cr-5Mo-5V-4Al (wt.%) (Ti-6554) [9,[11][12][13][14][15][16][17]. Figure 1(a) illustrates the deleterious effects on mechanical properties associated with i precipitation in 24 h aged Ti-24-Nb-4Zr-8Sn wt.% (Ti-2448) [10].…”
mentioning
confidence: 99%
“…In our recent studies, coupling atom probe and aberration-corrected scanning transmission electron microscope, several novel phase transformation mechanisms have been systematically explored in a beta titanium alloy, Ti-5Al-5Mo-5V-3Cr (Ti-5553, wt.%) [1][2][3][4]. It has been clearly shown that the size, morphology and number density of hcp structure alpha precipitates in Ti-5553 can be significantly influenced by the nano-scale structural and compositional instability, more specifically the metastable hexagonal structure isothermal omega phase, present in parent bcc structure beta phase.…”
mentioning
confidence: 99%